Modeling organic fouling of reverse osmosis membrane: From adsorption to fouling layer formation - Li, Haigang; Xia, Huanjin; Mei, Yingxin (Desalination, 2016)
A combined model is developed for flux decline of reverse osmosis (RO) membranes, which accounts for initial fouling due to adsorption and subsequent fouling due to the growth of a fouling layer. The predicted data are in excellent agreement with the experimental ones obtained over crossflow filtration of organic wastewaters using aromatic polyamide RO membranes over the entire course of the filtration. The model also provides a smooth transition from the adsorption regime to the fouling layer filtration regime. Based on the flux profiles and the analysis of the membrane surface, a two-step fouling mechanism is proposed to describe the evolution of fouling during continuous crossflow operation of RO membranes. The development of membrane fouling. [Display omitted] •Adsorption/fouling-layer model analyzes the flux decline during RO filtration.•The model provided a qualitative appreciation of the flux decline.•The factors of filtration time and membrane flux are considered in the fouling model.•The main interfacial interaction in each fouling step was discussed.